Co-Precipitation Synthesis and Analysis of Co and Zn Doped Barium M-Hexaferrites - Pangga, Dwi; Pathoni, Haerul; Suprianto, Suprianto (Universitas Pendidikan Mandalika, 2024)
Barium hexaferrite (BaFe12O19) is a material of significant interest due to its wide range of applications. In this study, we synthesized barium M-hexaferrites (BaFe12-2xCoxZnxO19) powders through the co-precipitation method, starting from BaCO3 and FeCl3.6H2O powders, with Co and Zn powders used as dopant materials. The variations in x values were set at 0, 0.2, 0.4, 0.6, 0.8, and 1. Our findings indicate that the co-precipitation method is highly effective for synthesizing barium M-hexaferrites (BaFe12-2xCoxZnxO19) nanomaterials, which contain more than 89% iron elements and have an average particle size of 50 nm. The Differential Thermal Analysis (DTA) and Thermogravimetric Analysis (TGA) reveal that phase transformations occur at temperatures of 285°C and in the range of 750-840°C. Further analysis using the Rietveld refinement method demonstrates that the barium M-hexaferrite phase begins to form at relatively low temperatures, with the most optimal yield observed at x = 0.4. At temperatures exceeding 740°C, there is a tendency to form a single-phase α-Fe2O3 (hematite). The introduction of Co and Zn as dopant ions results in only minor changes to the lattice parameters of the basic hexagonal crystal structure. This comprehensive study underscores the viability of the co-precipitation method for producing high-quality barium M-hexaferrites and provides valuable insights into the effects of Co and Zn doping on the structural and thermal properties of these materials.